(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the average prevalence of errors in the preparation and administration of intravenous medications in a hospital by means of a meta-analysis. Method: Systematic review through meta-analysis with meta-regression, registered in PROSPERO (CRD42022324431), with a search in the seven databases, using the Rayyan QCRY®. The methodological quality of the selected studies was assessed using the Newcastle-Ottawa Scale. The meta-analysis was calculated using the random-effect model and adjusted by the inverse of the variance, and analyses were carried out to investigate heterogeneity. Results: 34 primary studies were included. The estimated prevalence of errors in the preparation and administration of intravenous drugs was 41,23% (IC95% 30,51–51,96; I2 = 100,00%). Conclusion: The results reflect the lack of health systems official data on the reporting of errors in institutions, the basis for the effective strategies that ensure for patient safety in the process medicated.